Paid Paying Practices In 'Urf Perspective In Risa and Kalampa Villages, Woha District, Bima Regency West Nusa Tenggara Province - Ahmad Imam Hambali; Masithoh Masithoh (Ridwan Institute, 2022)
Pawning fields in Risa and Kalampa Villages, Woha District, Bima Regency, West Nusa Tenggara Province is a debt agreement between the pawner and the recipient of the pawn. Pawning rice fields have been going on for a long time and have become a local community tradition because it is considered to have social value. This study aims to determine and determine the law of the practice of pawning from the perspective of 'urf. This research is descriptive qualitative with a normative sociological approach. The results showed that First, the practice of pawning the fields in Risa and Kalampa villages is a debt agreement between the rain (pawner) and curtain (pawn recipient) in which the pawnbroker (rahin) will provide a guarantee in the form of rice fields to the pawn recipient (murtahin). Second, if viewed from the perspective of 'urf, this practice of pawning belongs to the category of 'urf, which is faced (damaged) because the recipient of the pawn (murtahin) does not ask for permission either verbally or in writing to the pawner (rahin) regarding the management of rice fields that are used as collateral for the debt. In the sharia economic literature, the practice of pawning fields like this is included in the category of usury because they get property in a vanity way, namely, in addition to the recipient of the pawn (murtahin) getting their money back, there is also an attempt to exploit the collateral field belonging to the pawner (rahin) in order to get multiple benefits